Effects of Al on microstructure and mechanical properties of hot-extruded Mg–3Nd alloys. Issue 3 (11th February 2023) - Yu, Peichen; Wang, Lei; Wang, Liping; Feng, Yicheng; Fu, Yuanke; Zhao, Sicong; Guo, Erjun; Wang, Zhiwei
Abstract : The effects of Al content on microstructure, texture, and mechanical properties of as-extruded Mg–3Nd alloy were investigated. The particle stimulated nucleation effect of Al2 Nd and Al11 Nd3 phases promotes dynamic recrystallisation and the texture is weakened of the as-extruded alloys. With the increase in Al content in the alloys, the microstructure transformed from a bimodal structure to an almost fully recrystallised structure. Grain refinement, the distribution of the second phases, and texture are important factors determining the mechanical properties of as-extruded alloys. As-extruded Mg–3Nd–3Al achieved a good balance of strength and plasticity. The ultimate tensile strength, yield strength, and elongation are 283, 221.3 MPa, and 15.7%, respectively.